Massively Introduced Managed Species and Their Consequences for Plant–Pollinator Interactions - Geslin, Benoît; Gauzens, Benoit; Baude, Mathilde; Dajoz, Isabelle; Fontaine, Colin; Henry, Mickaël; Ropars, Lise; Rollin, Orianne; Thébault, Elisa; Vereecken, Nicolas J. (Advances in ecological research, 2017)
Since the rise of agriculture, human populations have domesticated plant and animal species to fulfil their needs. With modern agriculture, a limited number of these species has been massively produced over large areas at high local densities. Like invasive species, these Massively Introduced Managed Species (MIMS) integrate local communities and can trigger cascading effects on the structure and functioning of ecosystems. Here, we focus on plant and insect MIMS in the context of plant–pollinator systems. Several crop species such as mass flowering crops (e.g. Brassica napus) and domesticated pollinating insects (e.g. Apis mellifera, Bombus terrestris) have been increasingly introduced worldwide and their impact on natural communities is addressed by an increasing number of scientific studies. First, we review the impacts of major insect and plant MIMS on natural comm- unities by identifying how they affect other species through competition (direct and apparent competition) or facilitation (attraction, spillover). Second, we show how MIMS can alter the structure of plant–pollinator networks. We specifically analysed the position of A. mellifera from 63 published plant–pollinator webs to illustrate that MIMS can occupy a central position in the networks, leading to functional consequences. Finally, we present the features of MIMS in sensitive environments ranging from oceanic islands to protected areas, as a basis to discuss the impacts of MIMS in urban context and agrosystems. Through the case study of MIMS in plant–pollinator interactions, we thus provide here a first perspective of the role of MIMS in the functioning of ecosystems.